2021
DOI: 10.1007/s40831-021-00383-x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Recycling of End-of-Life Dolomite Refractories by the Production of Geopolymer-Based Composites: Experimental Investigation

Abstract: Production and characterization of geopolymers prepared by mixing metakaolin, end-of-life dolomite refractories, sodium silicate solution, and sodium hydroxide solution have been performed. The as-received refractory was crumbled in order to obtain products having, respectively, 250 μm, 1 mm, and 2.5 mm maximum particles size. Each batch of powder was added in different proportions to a blank geopolymeric matrix. It has been observed that the addition of waste refractory reduces workability of the reference re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In agreement with the approach followed in a previous research [22], geopolymeric monoliths have been produced using alkali-activated metakaolin (MK) which was mixed with different proportions of waste OS. Samples were prepared using either the as-received OS, or after a thermal treatment at 900 °C which was made to remove the residual organic compounds still present in the as-received waste olivine sands.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In agreement with the approach followed in a previous research [22], geopolymeric monoliths have been produced using alkali-activated metakaolin (MK) which was mixed with different proportions of waste OS. Samples were prepared using either the as-received OS, or after a thermal treatment at 900 °C which was made to remove the residual organic compounds still present in the as-received waste olivine sands.…”
Section: Introductionmentioning
confidence: 78%
“…In addition, Table 2 also contains the Na 2 SiO 3 /NaOH ratio which is 3.4. The mix proportion design was built up on the base of previous research investigations [22,23].…”
Section: Preparation and Characterization Of The Starting Materialsmentioning
confidence: 99%
“…Several formulations were tested in this work but, for the sake of brevity, only the best performing formulations for each type of geopolymer (acid/alkaline) will be reported. Compositions listed in Table 1, in fact, had both good mechanical properties and pore size distributions suitable for stimulating osteointegrative phenomena [4,[22][23][24].…”
Section: Geopolymers Formulations and Dip Coating Processmentioning
confidence: 99%
“…FCA has also been reported to be partially studied as a building material; however, most studies suggest its use as a binder material (with GGBS, FA, OPC, Lime, Red Mud). In several studies, authors have reported its use as a substitute for cement by Mishra et al 2020b, Kumar et al 2020, Acharya and Patro 2016a, Machiels et al 2017, Mishra et al 2022a, Mishra et al 2022c, Acharya and Patro 2016c, Saha et al 2021, Acharya and Patro 2016d, Sharma et al 2022, and as a precursor material in geopolymers and alkali-activated materials by Rangan 2014, Mishra et al 2022a, Phoongernkham et al 2014, York and Europe 2021, Furlani et al 2021, Acharya and Patro 2015, Acharya and Patro 2016c.…”
Section: Introductionmentioning
confidence: 99%